Early-life adversity and orbitofrontal and cerebellar volumes in adults with obsessive–compulsive disorder: Voxel-based morphometry study. (January 2016) - Brooks, Samantha J.; Naidoo, Vanesh; Roos, Annerine; Fouché, Jean-Paul; Lochner, Christine; Stein, Dan J.
Abstract : Background: Early-life adversity is a risk for obsessive–compulsive disorder (OCD), but the impact at the neural level is less clear. Aims: To investigate the association between brain volumes and early-life adversity in individuals with a diagnosis of OCD only. Method: The Childhood Trauma Questionnaire (CTQ-28) was used to assess early-life adversity in 21 participants with OCD and 25 matched healthy controls. The relationship between global and regional brain volume and early-life adversity was measured using voxel-based morphometry (VBM). All data were corrected for multiple comparisons using family-wise error (FWE) at P <0.05. Results: In the OCD group, correlations with total CTQ scores were positively associated with a larger right orbitofrontal cortex volume. Physical neglect was higher in the OCD group than in controls and was positively associated with larger right cerebellum volume in the OCD group only. Conclusions: Larger brain volumes may reflect underlying developmental neuropathology in adults with OCD who also have experience of childhood trauma.